Bimetal metal-organic framework hollow nanoprisms for enhanced electrochemical oxygen evolution. (1st February 2023) - Sun, Fengzhan; Xu, Hao; Zhu, Wen; Lu, Chong; Ren, Li; Chong, Lina; Zou, Jianxin
Abstract: Carboxylate-based metal-organic frameworks (MOFs) have emerged as promising electrocatalyst candidates for the water splitting and metal-air batteries. Hierarchical porous structure and redox-active metal centers with unsaturated coordination sites in MOFs facilitate the enhanced catalytic activity of oxygen evolution reaction (OER). Herein, uniform hollow structured Fe-free bi-metal (Co, Ni) MOF-74 nanoprisms are successfully synthesized using a solvothermal method and (Co1 Ni1 )3 (OH)(CH3 COO)5 as the sacrificial templates, where Co and Ni are the metal nodes and 2, 5-dihydroxyterephthalic acid (H4 DOBDC) serves as the organic ligand. At an overpotential of 300 mV, CoNi MOF-74 shows a high electrocatalytic activity towards OER in 0.1 M KOH, where the current density is 10 mA cm −2 and the Tafel slope is 65.6 mV dec −1 . Meanwhile, CoNi MOF-74 is durable that sustains in alkaline for 100 h with 83.25% retention of current density. The improved catalytic activity can be associated with the in-situ generated amorphous Ni–Co (oxy)hydroxide, as well as the electron transfer from Ni 2+ to Co 2+ . This work elucidates the potential application of MOF materials as efficient electrocatalysts for OER. Graphical abstract: Image 1 Highlights: A hollow structured bi-metal organic framework of CoNi MOF-74 is synthesized using a template sacrifice method. Hierarchical porous structure and metal-metal interaction effectively improve OER catalytic performances. The optimized MOF-74 exhibits high OER activity and retains 83.25% of the initial current density after 100 h in 0.1 M KOH. The structure reconstruction of MOFs and partial oxidation of metal cations during OER process are carefully investigated.